Colloidal particles at fluid interfaces: behaviour of isolated particles. Issue 6 (2nd January 2019) - Ballard, Nicholas; Law, Adam D.; Bon, Stefan A. F.
Abstract : We review the adsorption of colloidal particles at fluid interfaces, highlighting the effects of particle shape and chemistry. Abstract : The adsorption of colloidal particles to fluid interfaces is a phenomenon that is of interest to multiple disciplines across the physical and biological sciences. In this review we provide an entry level discussion of our current understanding on the physical principles involved and experimental observations of the adsorption of a single isolated particle to a liquid–liquid interface. We explore the effects that a variation of the morphology and surface chemistry of a particle can have on its ability to adhere to a liquid interface, from a thermodynamic as well as a kinetic perspective, and the impact of adsorption behaviour on potential applications. Finally, we discuss recent developments in the measurement of the interfacial behaviour of nanoparticles and highlight open questions for future research.